2001
DOI: 10.1001/archpsyc.58.4.334
|View full text |Cite
|
Sign up to set email alerts
|

Neural Activity Related to Drug Craving in Cocaine Addiction

Abstract: The collected findings suggest the craving-related activation of a network of limbic, paralimbic, and striatal brain regions, including structures involved in stimulus-reward association (amygdala), incentive motivation (subcallosal gyrus/nucleus accumbens), and anticipation (anterior cingulate cortex).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
371
3
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 511 publications
(411 citation statements)
references
References 38 publications
35
371
3
2
Order By: Relevance
“…[2][3][4][5] In humans, neuroimaging studies have revealed cocaine-induced functional activation of the NAc following acute drug administration in cocaine-dependent subjects 6 and bilateral activation of the NAc following imagery-induced drug craving. [6][7][8] These data support numerous studies in animal models demonstrating the role of the NAc in the reinforcing effects of cocaine. [9][10][11][12][13][14] Although regional and neurotransmitter-centric hypotheses have provided a framework for studying the acute and chronic effects of cocaine intake on the brain, detailed mechanisms of intracellular neuroadaptations have only recently become known.…”
Section: Introductionsupporting
confidence: 79%
“…[2][3][4][5] In humans, neuroimaging studies have revealed cocaine-induced functional activation of the NAc following acute drug administration in cocaine-dependent subjects 6 and bilateral activation of the NAc following imagery-induced drug craving. [6][7][8] These data support numerous studies in animal models demonstrating the role of the NAc in the reinforcing effects of cocaine. [9][10][11][12][13][14] Although regional and neurotransmitter-centric hypotheses have provided a framework for studying the acute and chronic effects of cocaine intake on the brain, detailed mechanisms of intracellular neuroadaptations have only recently become known.…”
Section: Introductionsupporting
confidence: 79%
“…The amygdala is one of the few brain regions that consistently exhibit increased metabolic activity in response to cocaine-associated cues in both animal (Brown et al, 1992;Ciccocioppo et al, 2001) and human (Childress et al, 1999;Kilts et al, 2001) studies, consistent with this region's role in conditioned emotional memories. In preclinical studies, the infusion of scopolamine into the BLA just prior to the acquisition phase of a classical conditioning procedure produced a dose-dependent disruption of cocaine-seeking behavior during cue-induced drug reinstatement (See et al, 2003).…”
Section: Acetylcholine and Conditioned Learningmentioning
confidence: 59%
“…These include various portions of the cingulate gyrus (Breiter et al, 1997;Childress et al, 1999;Garavan et al, 2000;Grant et al, 1996;Kilts et al, 2001;Mass et al, 1998;Wexler et al, 2001;Brody et al, 2002), the orbital cortex (Grant et al, 1996;Mass et al, 1998;Wang et al, 1999), the nucleus accumbens (Breiter et al, 1997;George et al, 2001;Kilts et al, 2001), and the insula (Breiter et al, 1997;Wang et al, 1999).…”
Section: Discussionmentioning
confidence: 99%